Dive Into the Challenges of Law Enforcement of The Notary Code of Conduct in the Digital Age - Syauqina Maghfirah Salsabila; Dory Aprilya Subroto; Ninik Pratiwi (IHSA Institute, 2022)
The purpose of this study is to analyze the problems faced by notaries in implementing the code of ethics in the digital era and what are the problems of law enforcement of the notary code of ethics in the digital era. This research is normative juridical research using statutory, conceptual, and case approaches and analyzed descriptively qualitatively. The results of the analysis show that the digitalization era which is dominated by social media platforms can be an opportunity for Notaries to simplify their performance, but on the other hand it also opens up new potential for Notaries to take actions that violate the Notary's code of ethics. That is why the existence of the Notary Supervisory Council is very necessary to really carry out supervision and action against notaries who violate the code of ethics. The problem that has been experienced in the context of law enforcement of the notary code of ethics is that so far MPM seems to work half-heartedly, so that many notaries do not heed the warnings or sanctions given when they are found to have violated the Notary Code of Ethics.